France 2026 - Bryant, Jon (Travel writer); Bryant, Jon (Travel writer); Parry, Lyn; Burgot, Elisabeth Blanchet; Richards, Anna (Travel writer) (Eyewitness travel guides., 2025)
Few countries capture the imagination quite like France. The world-famous cuisine is as rich and varied as the glorious landscapes, the wine as renowned and captivating as the art. From the alpine peaks to the Mediterranean beaches, each region has its own robust history and lively culture to inspire visitors. Our updated guide brings France to life, transporting you there like no other travel guide does with expert-led insights, trusted travel advice, detailed breakdowns of all the must-see sights, photographs on practically every page, and our hand-drawn illustrations which place you inside the country's iconic buildings and neighborhoods.